Environmentally friendly adhesive resin produced using a low carbon emission process, adhesive composition containing the same, and adhesive layer formed using the same
The low-carbon emission process for producing environmentally friendly pressure-sensitive adhesive resin through a core-shell structured colloidal adhesive resin addresses the high energy consumption and emissions in traditional adhesive manufacturing, achieving strong and heat-resistant adhesives with reduced solvent and energy use.
Patent Information
- Application Number
- JP2024549247
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-06-29
- Filing Date
- 2023-03-17
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Current adhesive manufacturing processes consume a significant amount of energy and result in high greenhouse gas emissions due to the use of large solvents for polymerization and viscosity adjustment.
A low-carbon emission process is developed to produce an environmentally friendly pressure-sensitive adhesive resin using a core-shell structured colloidal adhesive resin, which involves polymerizing hydrophilic and hydrophobic monomers to form an amphiphilic polymer and then adding a hydrophobic monomer to create a colloidal resin with reduced solvent usage.
The process significantly reduces solvent usage and energy consumption, resulting in an adhesive with superior adhesive strength and heat resistance while minimizing carbon emissions.
Smart Images

Figure 2025507429000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an environmentally friendly adhesive resin produced using a low-carbon emission process, an adhesive composition containing the same, and an adhesive layer formed using the same. More specifically, the present invention relates to a method for producing an environmentally friendly adhesive resin using a low-carbon emission process that can reduce greenhouse gas emissions by using a smaller amount of solvent than conventional techniques, an adhesive resin produced thereby, an adhesive composition containing the adhesive resin, and an adhesive layer formed using the same. [Background technology]
[0002] As environmental pollution and climate change issues have become more serious recently, the international community has been discussing ways to reduce carbon emissions. In relation to this, at the 48th IPCC General Assembly in 2018, the Intergovernmental Panel on Climate Change (IPCC) presented a path to reduce CO2 emissions by at least 45% by 2030 compared to 2010 levels. This issue of carbon emissions is also a major issue in chemical-based fields such as adhesives, and there is growing interest in reducing carbon in manufacturing processes and products.
[0003] Generally, adhesives are composed of resins produced by polymerizing monomers in a solvent, solvents, hardeners, etc., and in the adhesive manufacturing process, a large amount of solvent is used for resin polymerization and viscosity control, and temperature control is required for polymerization and adhesive layer formation. As a result, there is a problem that a considerable amount of energy is consumed for heating and drying during adhesive manufacturing, which causes carbon emissions, so there is a need to develop technology to reduce carbon emissions in the adhesive manufacturing process.
[0004] Meanwhile, conventional environmentally friendly adhesive manufacturing technologies have been developed to eliminate the use of highly harmful solvents (e.g., toluene) as described in Korean Patent Publication No. 10-2012-0051596, or to manufacture water-based adhesives dispersed in water as described in Korean Patent Publication No. 10-1115681. However, these technologies were limited in that they were aimed at reducing the harmfulness of the adhesive itself and did not recognize the purpose of reducing carbon emissions during manufacturing processes such as heating and drying.
[0005] As such, the development of technology to reduce the amount of carbon emitted from the adhesive manufacturing process is still in progress, and the development of low-carbon processes is urgently needed to comply with measures such as carbon emission regulations. Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a method for producing an adhesive resin having excellent physical properties and being environmentally friendly in a low carbon emission process.
[0007] Another object of the present invention is to provide an environmentally friendly adhesive resin produced by said method.
[0008] Another object of the present invention is to provide a pressure-sensitive adhesive composition comprising said environmentally friendly pressure-sensitive adhesive resin.
[0009] Another object of the present invention is to provide a pressure-sensitive adhesive layer produced using the environmentally friendly pressure-sensitive adhesive resin. [Means for solving the problem]
[0010] In order to achieve the above object, the present invention provides an environmentally friendly method for producing an adhesive resin, comprising: (i) polymerizing a hydrophilic monomer and a hydrophobic monomer to produce an amphiphilic polymer; and (ii) adding a hydrophobic monomer to the amphiphilic polymer and reacting the polymer to produce a colloidal adhesive resin having a core including a hydrophobic monomer and a shell including an amphiphilic polymer.
[0011] In step (i), the weight ratio of the hydrophilic monomer to the hydrophobic monomer may be 1:1 to 1:15.
[0012] In step (i), the hydrophilic monomer may include at least one monomer having at least one functional group selected from the group consisting of a carboxyl group, a hydroxyl group, an amine, and an ether in the molecule.
[0013] The hydrophobic monomers in steps (i) and (ii) may each independently include one or more monomers selected from the group consisting of vinyl ester monomers and alkyl (meth)acrylate monomers.
[0014] In the step (ii), 20 parts by weight or less of a hydrophilic monomer may be further added to 100 parts by weight of the hydrophobic monomer added to the amphiphilic polymer.
[0015] The total weight of the monomers used in step (ii) may be 200 to 500 parts by weight based on 100 parts by weight of the total weight of the monomers used in step (i).
[0016] The reactions in steps (i) and (ii) can be carried out in a solvent.
[0017] In the step (i), 50 to 200 parts by weight of the solvent may be used based on 100 parts by weight of the total weight of the monomers.
[0018] In the step (ii), 10 to 150 parts by weight of the solvent may be used based on 100 parts by weight of the total weight of the monomers.
[0019] The boiling point of the solvent used in the reactions in steps (i) and (ii) is preferably 80° C. or lower.
[0020] The solvents used in the reactions of steps (i) and (ii) may each independently be a mixed solvent containing ethyl acetate and one or more cosolvents.
[0021] The reactions in steps (i) and (ii) may be carried out using a polymerization initiator.
[0022] The present invention also provides an environmentally friendly adhesive resin produced by the above method.
[0023] The present invention also provides an environmentally friendly adhesive composition comprising the above-mentioned environmentally friendly adhesive resin and a curing agent.
[0024] In the present invention, the curing agent can be contained in an amount of 0.01 to 5 parts by weight based on 100 parts by weight of the adhesive resin.
[0025] In the present invention, the pressure-sensitive adhesive composition may further include a coating solvent.
[0026] In the present invention, the coating solvent may be contained in an amount of 5 to 40 parts by weight based on 100 parts by weight of the adhesive resin.
[0027] The present invention also provides an environmentally friendly adhesive layer formed using the environmentally friendly adhesive resin.
[0028] In the present invention, the pressure-sensitive adhesive layer may have a thickness of 5 to 500 μm. Effect of the Invention
[0029] The method for producing an adhesive resin of the present invention uses less solvent than conventional processes, and when diluting the resin with a solvent for adhesive application, the viscosity can be smoothly reduced even with a small amount of solvent. In addition, since the resin can be produced with a low boiling point solvent, the time consumed for drying the adhesive layer can be reduced, and the adhesive produced using the present invention exhibits superior adhesive strength and heat resistance compared to adhesives produced using conventional processes. Therefore, the present invention can produce an adhesive with excellent physical properties using an environmentally friendly process that significantly reduces carbon emissions. [Brief description of the drawings]
[0030] [Figure 1] FIG. 1 is a schematic diagram illustrating an environmentally friendly adhesive resin manufacturing process according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] The specific embodiment of the present invention will be described in more detail below.Unless otherwise defined, all technical and scientific terms used herein have the same meaning as that commonly understood by a skilled artisan in the field to which the present invention belongs.Generally, the nomenclature used herein is that which is well known and commonly used in the art.
[0032] The present invention relates to a method for producing an adhesive resin that is environmentally friendly by applying a low carbon emission process.
[0033] The adhesive resin of the present invention has a high concentration and excellent productivity, and when diluted with a solvent for coating, the viscosity is smoothly reduced even with a small amount of solvent. This allows the amount of solvent used to be reduced, the solvent content per unit area during coating is low, and the energy used for volatilization of the solvent can be reduced. In addition, when a low boiling point solvent is used, the drying temperature can also be lowered, so energy consumption can be further reduced. In addition, by using the adhesive resin of the present invention, an adhesive layer (tape, film, etc.) with excellent adhesion and heat resistance can be produced.
[0034] The present invention is characterized by the use of amphiphilic polymers and hydrophobic monomers to prepare colloidal adhesive resins with a core-shell structure.
[0035] Specifically, the method for producing an environmentally friendly adhesive resin of the present invention includes the steps of: (i) polymerizing a hydrophilic monomer and a hydrophobic monomer to produce an amphiphilic polymer; and (ii) adding a hydrophobic monomer to the amphiphilic polymer and reacting the polymer to produce a colloidal adhesive resin having a core including a hydrophobic monomer and a shell including an amphiphilic polymer.
[0036] FIG. 1 is a schematic diagram showing a method for manufacturing a pressure-sensitive adhesive resin according to the present invention. Referring to FIG. 1, when a relatively hydrophobic monomer is added to an amphipathic polymer obtained by polymerizing a hydrophilic monomer and a hydrophobic monomer, a state in which the amphipathic polymer material and the hydrophobic monomer are mixed is formed. When the reaction proceeds in this state, the amphipathic polymer and the hydrophobic monomer begin to form a core-shell structure, and a micelle is formed by the amphipathic polymer forming the shell. As the polymerization of the hydrophobic monomer proceeds and the molecular weight increases, the hydrophobic monomer is located inside the micelle, and polymerization proceeds. As a result, a colloidal pressure-sensitive adhesive resin with a core-shell structure is produced.
[0037] In step (i), the hydrophilic monomer may include at least one monomer having at least one functional group, such as a carboxyl group, a hydroxyl group, an amine, or an ether, in the molecule.
[0038] Specifically, examples of the hydrophilic monomer include acrylic acid (AA), methacrylic acid (MAA), β-carboxyethyl acrylate (β-CEA), itaconic acid, fumaric acid, maleic acid, 2-hydroxyethyl acrylate (2-HEA), 2-hydroxyethyl methacrylate (2-HEMA), 2-hydroxypropyl acrylate (2-HPA), 2-hydroxypropyl methacrylate (2-HPMA), 4-hydroxybutyl acrylate (4-HBA), polyethylene glycol mono(meth)acrylate, acryloylmorpholine (acryloyl ethyl acrylate), 2-hydroxypropyl acrylate (2-HPA), 2-hydroxypropyl methacrylate (2-HPMA), 4-hydroxybutyl acrylate (4-HBA), polyethylene glycol mono(meth)acrylate, 2-hydroxypropyl acrylate (2-HPA), 2-hydroxypropyl methacrylate (2-HPMA), 4-hydroxybutyl acrylate (4-HBA), 2-hydroxypropyl acrylate (2-HPA), 2-hydroxypropyl methacrylate (2-HPMA), 2-hydroxypropyl ... One or more of the following may be used: morpholine (ACMO), 2-(dimethylamino)ethyl methacrylate (DMAE(M)A), polyethylene glycol monomethyl ether(meth)acrylate (MPEG(M)A), 2-(2-ethoxy ethoxy)ethyl(meth)acrylate (EOEOE(M)A), and the like.
[0039] In step (i), the hydrophobic monomer may be a monomer having a water solubility (based on 20° C.) of 5 g / 100 mL or less, and may include at least one of vinyl ester monomers, alkyl (meth)acrylate monomers, etc., and preferably at least one of vinyl ester monomers, alkyl (meth)acrylate monomers, etc. having 4 to 24 carbon atoms.
[0040] For example, the hydrophobic monomer may be one or more of vinyl acetate (VA), methyl acrylate (MA), ethyl acrylate (EA), butyl acrylate (BA), 2-ethylhexyl acrylate (2-EHA), lauryl methacrylate (LMA), cyclohexyl methacrylate (CHMA), isooctyl acrylate, stearyl acrylate, vinyl 2-ethylhexanoate, and the like.
[0041] In step (i), the hydrophilic monomer and the hydrophobic monomer may be mixed in a weight ratio of 1:1 to 1:15, preferably 1:2.5 to 1:12. Within this range, an amphiphilic polymer suitable for the subsequent process may be formed by polymerization of the hydrophilic monomer and the hydrophobic monomer.
[0042] In step (i), the hydrophilic monomer and the hydrophobic monomer are reacted in a solvent, and the reacted monomer is dispersed in the solvent. The solvent may be an organic solvent such as an ester, ketone, or alcohol, and is preferably a low-boiling solvent having a boiling point of 80° C. or less. The low-boiling solvent may be one or more of ethyl acetate (boiling point 77.1° C.), ethyl alcohol (boiling point 78.4° C.), acetone (boiling point 56.0° C.), methanol (boiling point 64.7° C.), methyl ethyl ketone (boiling point 79.6° C.), etc.
[0043] In the present invention, when the solvent is to be recovered and reused, ethyl acetate can be used alone as a solvent, or a two-type mixed solvent obtained by mixing ethyl acetate with a cosolvent such as acetone or ethanol can be used. By using the cosolvent, the reaction temperature can be lowered and the amount of expensive ethyl acetate used can be reduced. When using two types of mixed solvent, ethyl acetate and the cosolvent can be mixed in a weight ratio of 5:5 to 9:1, preferably 6:4 to 8:2.
[0044] The solvent can be used in an amount of 50 to 200 parts by weight, specifically 80 to 150 parts by weight, based on 100 parts by weight of the total monomers used in step (i).
[0045] In step (i), a polymerization initiator may be added for polymerization of the hydrophilic monomer and the hydrophobic monomer, which serves to generate radicals and induce a crosslinking reaction.
[0046] The polymerization initiator is an additive that initiates polymerization of a monomer by heat or light, and may be a thermal polymerization initiator or a photopolymerization initiator. A thermal polymerization initiator is preferably used.
[0047] For example, in the present invention, as the polymerization initiator, one or more of the following can be used: azo-based initiators such as 2,2-azobisisobutyronitrile, 2,2-azobis-2-methylbutyronitrile, 2,2-azobis-2,4-dimethylvaleronitrile; peroxyester-based initiators such as dipropyl peroxydicarbonate, diisopropyl peroxydicarbonate, bis-4-butylcyclohexyl peroxydicarbonate, diethoxyethyl peroxydicarbonate; and peroxydicarbonate compounds such as dimethylhydroxybutyl peroxyneodecanoate, amyl peroxyneodecanoate, butyl peroxyneodecanoate.
[0048] The polymerization initiator can be used in an amount of 0.05 to 3 parts by weight, preferably 0.1 to 2 parts by weight, based on 100 parts by weight of the total monomers used in step (i).
[0049] In step (i), the monomers are reacted to form an amphiphilic polymer. For example, when a thermal polymerization initiator is used, the polymerization reaction can be initiated by raising the temperature of the reaction mixture. Specifically, the reaction temperature can be raised to 50 to 100°C, preferably 70 to 90°C, and the polymerization is completed through a maintenance reaction for 10 to 90 minutes, preferably 15 to 60 minutes.
[0050] By polymerizing a hydrophilic monomer and a hydrophobic monomer according to step (i), an amphiphilic polymer in which a hydrophilic portion and a hydrophobic portion coexist in one molecule is obtained.
[0051] Next, a hydrophobic monomer is added to the prepared amphiphilic polymer and reacted to prepare a colloidal adhesive resin.
[0052] Examples of the hydrophobic monomer that can be used in step (ii) include the monomers described in the description of step (i). The hydrophobic monomer added in step (ii) may be the same as or different from the hydrophobic monomer used in preparing the amphiphilic polymer in step (i).
[0053] When the hydrophobic monomer is added, the hydrophobic monomer is located inside the amphiphilic polymer while forming a core due to the difference in properties between the hydrophobic monomer and the amphiphilic polymer. As a result, a colloidal adhesive resin including a core containing the hydrophobic monomer and a shell containing the amphiphilic polymer is prepared. The adhesive resin is a non-aqueous dispersion (NAD) polymer phase, and the formation of the NAD polymer phase allows the preparation of a high-concentration adhesive with a relatively low viscosity, and the amount and content of solvent used in the adhesive layer preparation process can be reduced without deteriorating the physical properties, and the energy consumed for solvent evaporation per unit area can be reduced.
[0054] The weight of the hydrophobic monomer added in step (ii) may be 180 to 500 parts by weight, specifically 230 to 450 parts by weight, based on 100 parts by weight of the monomer used in preparing the amphiphilic polymer in step (i).
[0055] In step (ii), a small amount of hydrophilic monomer may be added. The types of hydrophilic monomers that can be used in step (ii) include the monomers described in the description of step (i), and the hydrophilic monomer added in step (ii) may be the same as or different from the hydrophilic monomer used in preparing the amphiphilic polymer in step (i).
[0056] The hydrophilic monomer may be added in an amount of 20 parts by weight or less, preferably 0.1 to 10 parts by weight, and more preferably 0.2 to 5 parts by weight, based on 100 parts by weight of the hydrophobic monomer added in step (ii). Within the above range, the viscosity can be more easily reduced by the coating solvent, and an adhesive resin having excellent adhesive strength of the tape can be produced. From this perspective, the hydrophilic monomer may be more preferably added in an amount of 0.5 to 3 parts by weight based on 100 parts by weight of the hydrophobic monomer.
[0057] The total weight of the monomers used in step (ii) may be 200 to 500 parts by weight, preferably 250 to 450 parts by weight, based on 100 parts by weight of the total weight of the monomers used in step (i).
[0058] In step (ii), a solvent and a polymerization initiator may be further added for reaction. Examples of the solvent and polymerization initiator that can be used in step (ii) include those described in the description of step (i), and the solvent and polymerization initiator used in step (ii) may be the same as or different from those used in step (i).
[0059] The solvent may be added in an amount of 10 to 150 parts by weight, specifically 20 to 100 parts by weight, based on 100 parts by weight of the total monomers added in step (ii).The polymerization initiator may be added in an amount of 0.05 to 5 parts by weight, preferably 0.1 to 3 parts by weight, based on 100 parts by weight of the total monomers added in step (ii).
[0060] After mixing the monomer mixture, a solvent and a polymerization initiator may be additionally added to completely react the unreacted monomers. The solvent and the polymerization initiator may be added in amounts ranging from 1 to 20 parts by weight and 0.05 to 3 parts by weight, respectively, based on 100 parts by weight of the total monomers added in step (ii).
[0061] In order to adjust the non-volatile matter (NVM) of the produced adhesive resin, a process such as adding a solvent can be further carried out. The non-volatile matter (solid content) of the finally produced adhesive resin can be at a level of 50 to 70% by weight, specifically 60% by weight, and at this time, it can show a viscosity of 2,000 to 10,000 cPs, preferably 2,000 to 8,000 cPs.
[0062] In the pressure-sensitive adhesive resin production process of the present invention (i.e., all processes including steps (i) and (ii)), the total weight of the solvent per 100 parts by weight of the total monomers used may be 30 to 100 parts by weight, preferably 50 to 80 parts by weight. According to the present invention, a pressure-sensitive adhesive resin having excellent physical properties can be produced while using a small amount of solvent compared to the monomers used.
[0063] Specifically, according to a general manufacturing process of adhesive resin, when the amount of solvent is reduced in the manufacturing process to adjust the non-volatile content to 45% by weight or more, there are drawbacks such as the adhesive resin not being obtained due to gelation of monomers during the reaction, or the viscosity exceeding 10,000 cPs under the condition of 60% by weight of non-volatile content, requiring a very large amount of coating solvent in the subsequent process. On the other hand, by using the process of the present invention, the non-volatile content can be adjusted to 50% by weight or more under the condition of a viscosity of 2,000 to 10,000 cPs, preferably 3,000 to 8,000 cPs, and a viscosity suitable for coating can be adjusted even with a small amount of solvent in the coating process.
[0064] Therefore, the use of the present invention can reduce the amount of organic solvent used, and in particular, even when a low-boiling point solvent is used, the reaction proceeds smoothly, and the greenhouse gas emissions emitted during the pressure-sensitive adhesive production process can be significantly reduced.
[0065] The reaction of step (ii) is terminated through the above method to produce a colloidal adhesive resin comprising a core containing a hydrophobic monomer and a shell containing an amphiphilic polymer. The present invention is excellent in resin productivity since it is possible to produce a high-concentration adhesive resin with a low carbon emission process. In addition, the adhesive resin of the present invention is highly concentrated, but the viscosity can be easily reduced with a small amount of solvent in the subsequent process, so the amount of solvent required for coating and the energy consumed for volatilizing the solvent after coating are low, and when used, an environmentally friendly adhesive with excellent adhesion and heat resistance can be produced.
[0066] The present invention also provides an environmentally friendly adhesive composition comprising the above-mentioned environmentally friendly adhesive resin.
[0067] The pressure-sensitive adhesive composition of the present invention comprises the pressure-sensitive adhesive resin produced by the present invention and a curing agent.
[0068] In the present invention, the curing agent may be one or more types of polyfunctional curing agents used in pressure-sensitive adhesive compositions, for example, curing agents selected from the group consisting of isocyanate-based compounds, epoxy-based compounds, aziridine-based compounds, and metal chelate-based compounds.
[0069] Specifically, the curing agent may be diphenylmethane-4,4'-diisocyanate, 1,3-xylene diisocyanate, 1,4-xylene diisocyanate, 1,3-bisisocyanatomethylcyclohexane, tetramethylxylene diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, xylene diisocyanate adduct of trimethylolpropane, toluene diisocyanate adduct of trimethylolpropane, hexamethylene diisocyanate of trimethylolpropane, isocyanurate of toluene diisocyanate (TDI isocyanurate), isocyanurate of hexamethylene diisocyanate (HDI isocyanurate), isocyanurate of isophorone diisocyanate (IPDI isocyanurate), isocyanurate); epoxy compounds such as ethylene glycol diglycidyl ether, triglycidyl ether, trimethylolpropane triglycidyl ether, N,N,N',N'-tetraglycidylethylenediamine, N,N,N',N'-tetraglycidylxylenediamine, and glycerin diglycidyl ether; aziridine compounds such as N,N'-toluene-2,4-bis(1-aziridinecarboxamide), N,N'-diphenylmethane-4,4'-bis(1-aziridinecarboxamide), triethylenemelamine, bisisoprotoyl-1-(2-methylaziridine), and tri-1-aziridinylphosphine oxide; and metal chelate compounds in which a polyvalent metal such as aluminum, iron, zinc, tin, titanium, antimony, magnesium, and / or vanadium is coordinated to acetylacetone or ethyl acetoacetate.
[0070] The curing agent can be used in an amount of 0.01 to 5 parts by weight, specifically 0.05 to 1 part by weight, based on 100 parts by weight of the adhesive resin. Within this range, the adhesive strength and other physical properties can be appropriately adjusted.
[0071] The pressure-sensitive adhesive composition of the present invention may further include a solvent for adjusting viscosity for coating. In the description of the present invention, the solvent used in the pressure-sensitive adhesive composition is referred to as a "coating solvent" to distinguish it from the solvent of the pressure-sensitive adhesive resin.
[0072] In the present invention, the coating solvent contained in the pressure-sensitive adhesive composition may be an organic solvent such as an ester, ketone, or alcohol. In particular, when a low-boiling point solvent having a boiling point of 80° C. or less is used as the coating solvent, it is preferable since the pressure-sensitive adhesive can be dried at a low temperature in the subsequent process. As the low-boiling point solvent, one or more of ethyl acetate, ethyl alcohol, acetone, methanol, etc. may be used.
[0073] The coating solvent can be used in an amount of 5 to 40 parts by weight, preferably 8 to 30 parts by weight, and more preferably 10 to 25 parts by weight, based on 100 parts by weight of the adhesive resin.
[0074] By adding the coating solvent, the viscosity of the pressure-sensitive adhesive composition can be adjusted to 500 to 3,000 cPs, preferably 1,000 to 2,000 cPs, thereby enabling the composition to exhibit coating properties suitable for forming a pressure-sensitive adhesive layer.
[0075] In the case of a general adhesive resin, in order to create a viscosity suitable for coating, a considerable amount of coating solvent must be added to dilute it, but the adhesive resin of the present invention has high viscosity characteristics and the viscosity decreases smoothly when the coating solvent is added. Therefore, according to the present invention, there are advantages in that the adhesive has excellent coating properties even when a small amount of coating solvent is mixed, and the amount of energy consumed for volatilization of the coating solvent is small.
[0076] In addition, the pressure-sensitive adhesive composition of the present invention may further contain one or more additives used to adjust the physical properties of the pressure-sensitive adhesive, such as a tackifier, a crosslinking catalyst, a silane coupling agent, etc. The additives may be used in an amount that does not affect the effects of the present invention, and may be contained in an amount of, for example, 0.0001 to 50 parts by weight per 100 parts by weight of the non-volatile content of the pressure-sensitive adhesive resin.
[0077] The present invention also provides an environmentally friendly adhesive layer formed using the adhesive resin. The adhesive layer is a layer formed by coating and drying an adhesive composition, and can be used in various forms such as an adhesive tape or an adhesive film.
[0078] The pressure-sensitive adhesive layer is formed by coating the pressure-sensitive adhesive composition of the present invention on a substrate. The thickness of the pressure-sensitive adhesive layer can be adjusted depending on the intended use, for example, in the range of 5 to 500 μm, preferably 10 to 200 μm.
[0079] The substrate on which the pressure-sensitive adhesive layer is formed can be selected depending on the form of use, such as a tape substrate, a release film, an adherend, etc. In addition, the substrate can be made of a material to which the pressure-sensitive adhesive composition can be applied, such as polyethylene terephthalate, polyethylene, polypropylene, polycarbonate, polyimide, polyurethane, etc. Among these, it is preferable to use polyethylene terephthalate, which is a rigid material, because it can provide a cushioning effect by absorbing impact.
[0080] The application of the pressure-sensitive adhesive composition may be carried out by various coating methods used in the field of pressure-sensitive adhesive coating, such as comma coating, doctor blade, bar coating, gravure coating, slot die coating, spin coating, etc. In particular, when a roll-to-roll process is used, comma coating, gravure coating, slot die coating, etc. are possible, so that production efficiency can be improved even when a low carbon emission process is applied.
[0081] After the pressure-sensitive adhesive composition is applied, the pressure-sensitive adhesive layer can be produced by drying at a temperature of 60 to 150°C, preferably 80 to 120°C, and more preferably 85 to 110°C. The drying process can be carried out for 30 to 240 seconds, preferably 60 to 120 seconds, and specifically 90 to 150 seconds.
[0082] After the drying process, a maturing process can be carried out at 30 to 60°C, and the maturing time can be adjusted to about 12 to 60 hours.
[0083] When using the present invention, coating is easy even with a low boiling point solvent when forming the adhesive layer, and the drying temperature can be set to a low temperature of 120° C. or less, preferably 110° C. or less, for example 100° C., and the produced adhesive layer exhibits excellent adhesive strength and heat resistance. In addition, since the amount of solvent used in the adhesive production process is small and the time consumed for volatilization is short, the adhesive can be produced in an environmentally friendly process with excellent production efficiency and low carbon emissions. EXAMPLES
[0084] The present invention will be described in more detail through the following examples. However, these examples are merely illustrative of some experimental methods and configurations for the purpose of illustrating the present invention, and the scope of the present invention is not limited to these examples.
[0085] <Production Example 1: Adhesive resin production>
[0086] <Example: Production of acrylic adhesive resin using non-aqueous dispersion>
[0087] To prepare the adhesive resin, a reaction flask equipped with a stirrer, a reflux condenser, a thermometer, and a dropping funnel was prepared.
[0088] After feeding the monomer mixture A into the reactor, 9.6g of ethyl alcohol and 18.4g of ethyl acetate were added to the mixture, and 0.1g of AIBN (azobisisobutyronitrile) was added as a polymerization initiator. After the addition, the temperature was raised to 80°C to start the reaction, and the reaction was continued for 30 minutes to form an amphiphilic polymer.
[0089] Next, monomer mixture B was added to the monomer dropping funnel, and 10.4g of ethyl alcohol, 17.6g of ethyl acetate, and 0.4g of polymerization initiator AIBN were mixed and added to the initiator dropping funnel, and then dropping was carried out for 90 minutes at the same time. After dropping was completed, a maintenance reaction was carried out for 60 minutes, and 10g of ethyl acetate and 0.3g of polymerization initiator AIBN were added to the initiator dropping funnel, and the mixture was dropped for 30 minutes to completely react the unreacted monomers. After the reaction, it was cooled and the non-volatile matter (NVM) was adjusted to a level of 60% with ethyl acetate, and the reaction was terminated.
[0090] As the reaction proceeded, it was observed that the amphiphilic polymer and the relatively hydrophobic monomer were converted into colloidal particles with a core-shell morphology, whereby the clear solution gradually took on a milky color.
[0091] The monomer composition used in the experiment and the physical properties of the synthesized adhesive are shown in Table 1. The viscosity was measured at 25°C according to ASTM D2196.
[0092] [Table 1]
[0093] <Comparative Example: Production of acrylic adhesive resin using general solution polymerization>
[0094] The same reactor as in the manufacturing example was prepared, and 30 g (30 wt%) of monomer mixture C was added to the reactor, and then 15 g of ethyl alcohol and 30 g of ethyl acetate were added to the mixture, and 0.5 g of AIBN (azobisisobutyronitrile) was added as a polymerization initiator. After the addition, the temperature was raised to 80°C to start the reaction, and the reaction was continued for 30 minutes.
[0095] Next, 70g (70wt%) of monomer mixture C, 21.5g of ethyl acetate, and 0.3g of polymerization initiator AIBN were dropped for 90 minutes. After the dropwise addition was completed, the reaction was maintained for 60 minutes, and 33g of ethyl acetate and 0.5g of polymerization initiator AIBN were dropped for 60 minutes, and the reaction was maintained for 3 hours before terminating, and the non-volatile content (NVM) was adjusted using ethyl acetate. The amount of solvent was reduced to adjust the non-volatile content to a level of 50-60%, but when the amount of solvent was reduced, the final product could not be obtained due to gelation of the monomer during the reaction, so a polymerizable amount of solvent was added to produce the resin.
[0096] The monomer composition used in the experiment and the physical properties of the synthesized adhesive are shown in Table 2. The viscosity was measured at 25°C according to ASTM D2196.
[0097] [Table 2]
[0098] <Experimental Example 1: Measurement of viscosity change according to the amount of solvent added>
[0099] In order to achieve a titration coating viscosity of 1,000-2,000 cPs during comma coating, the viscosity was measured according to the dilution amount of the solvent. The viscosity change was measured while adding ethyl acetate to 100 g of the adhesive resin obtained in the examples and comparative examples, and when it was confirmed that the viscosity had decreased to around 1,000 cPs, the experiment was terminated without adding any more solvent. The results of the viscosity change measurement are shown in Tables 3 and 4.
[0100] [Table 3]
[0101] [Table 4]
[0102] The experimental results showed that the adhesive of the present invention has a high solid content, but the viscosity can be adjusted to 2,000 cPs or less even with 15-20 g of solvent. In other words, the adhesive of the present invention uses a smaller amount of solvent than general adhesives, so carbon emissions are smaller and less energy is consumed to volatilize the solvent when forming the adhesive layer.
[0103] Meanwhile, in the case of the comparative adhesive produced using a general process, the solid content itself was low and the adhesive contained a large amount of solvent, but when diluting to adjust the adhesive viscosity, at least 25g of solvent was required. This shows that not only does the comparative adhesive resin use a large amount of solvent in the manufacturing process, but also that more energy is consumed to volatilize the solvent per unit area when manufacturing the adhesive layer.
[0104] According to the above experimental results, it can be confirmed that the amount of organic solvent required for coating can be reduced by using the adhesive resin of the present invention produced using a low carbon emission process.
[0105] <Production Example 2: Adhesive Tape Production>
[0106] To carry out comma coating, a pressure-sensitive adhesive composition was prepared by adding 0.5 g of a curing agent (Aekyung Chemical AK-75) and ethyl acetate to 100 g of the pressure-sensitive adhesive resin of Preparation Example 1. In the case of adding ethyl acetate to adjust the coating viscosity, 20 g was added to the pressure-sensitive adhesive resin of the embodiment, and 30 g was added to the pressure-sensitive adhesive resin of the comparative example.
[0107] To manufacture the adhesive tape, a 25 μm thick adhesive layer was formed using a comma coating device. A 25 μm thick PET film was used as the release film, and a 50 μm thick PET film was used as the base film.
[0108] After coating the adhesive layer, a drying step was carried out at 100° C. for 120 seconds, and then the adhesive tape was aged at 43° C. for 48 hours.
[0109] <Experimental Example 2: Comparison of adhesive tape properties>
[0110] The adhesive tape of Production Example 2 was measured for adhesive strength and heat resistance.
[0111] The adhesive strength was measured using a UTM device in accordance with KS T 1028. A 25 mm wide tape was pressed onto the SUS304 adhesive using a rubber roller with a load of 2.0 kg, and then the tape was left at room temperature for 30 minutes, and the 180°Peel value was measured at a speed of 300 mm / min.
[0112] For heat resistance, a 25 x 150 mm sample was prepared, and SUS was pressed onto the sample at a load of 2.0 kg to 25 x 25 mm, after which the sample was left at room temperature for 30 minutes. A load of 500 g was then applied, and the temperature was raised at 50°C at a rate of 10°C per 10 minutes, and the temperature at the time of desorption was recorded.
[0113] The room temperature adhesive strength and heat resistance of the pressure-sensitive adhesive tape measured in the above experiment are shown in Table 5 below.
[0114] [Table 5]
[0115] As a result of the experiment, when the adhesive resin prepared using the method of the present invention was used, the adhesive strength of the tape was at a similar level or even higher than when the adhesive resin prepared using the same monomer by a general solution polymerization method was used, and the adhesive strength tended to be excellent in heat resistance.
[0116] From these results, it was confirmed that when the low carbon emission process of the present invention is applied to the adhesive tape manufacturing process and an adhesive composition with a high non-volatile content is used, it is possible to manufacture an adhesive with better physical properties such as adhesive strength and heat resistance while reducing carbon emissions by using less solvent than conventional products.
[0117] Although some embodiments of the present invention have been described above, the present invention is not limited to the above-described embodiments, and can be modified and altered within the scope of the gist of the present invention. It should be understood that the embodiments to which such modifications and alterations are applied also belong to the technical spirit of the present invention.
Claims
1. (i) polymerizing a hydrophilic monomer and a hydrophobic monomer to prepare an amphiphilic polymer; and (ii) adding a hydrophobic monomer to the amphiphilic polymer and reacting the polymer to prepare a colloidal adhesive resin having a core including a hydrophobic monomer and a shell including an amphiphilic polymer; The method for producing an environmentally friendly adhesive resin includes the steps of:
2. In the step (i), 2. The method for producing an environmentally friendly adhesive resin according to claim 1, wherein the weight ratio of the hydrophilic monomer to the hydrophobic monomer is 1:1 to 1:
15.
3. In the step (i), 2. The method for producing an environmentally friendly adhesive resin according to claim 1, wherein the hydrophilic monomer comprises one or more hydrophilic monomers having one or more functional groups selected from the group consisting of a carboxyl group, a hydroxyl group, an amine, and an ether in the molecule.
4. 2. The method for producing an environmentally friendly adhesive resin according to claim 1, wherein the hydrophobic monomers in steps (i) and (ii) are each independently one or more hydrophobic monomers selected from the group consisting of vinyl ester monomers and alkyl (meth)acrylate monomers.
5. In the step (ii), 2. The method for producing an environmentally friendly adhesive resin according to claim 1, further comprising adding 20 parts by weight or less of a hydrophilic monomer to 100 parts by weight of the hydrophobic monomer added to the amphiphilic polymer.
6. 2. The method of claim 1, wherein the total weight of the monomers used in step (ii) is 200 to 500 parts by weight based on 100 parts by weight of the total weight of the monomers used in step (i).
7. The method for preparing an environmentally friendly adhesive resin according to claim 1, wherein the reactions in steps (i) and (ii) are carried out in a solvent.
8. In the step (i), The method for producing an environmentally friendly adhesive resin according to claim 7, wherein the solvent is used in an amount of 50 to 200 parts by weight per 100 parts by weight of the total weight of the monomers.
9. In the step (ii), The method for producing an environmentally friendly adhesive resin according to claim 7, wherein the solvent is used in an amount of 10 to 150 parts by weight per 100 parts by weight of the total weight of the monomers.
10. The method for producing an environmentally friendly adhesive resin according to claim 7, wherein the boiling point of the solvent is 80°C or lower.
11. The method for preparing an environmentally friendly adhesive resin according to claim 7, wherein the solvents in steps (i) and (ii) are each independently a mixed solvent comprising ethyl acetate and one or more cosolvents.
12. The method for preparing an environmentally friendly adhesive resin according to claim 1, wherein the reactions in steps (i) and (ii) are carried out using a polymerization initiator.
13. An environmentally friendly adhesive resin produced by the method according to any one of claims 1 to 12.
14. An environmentally friendly adhesive composition comprising the environmentally friendly adhesive resin of claim 13 and a curing agent.
15. The environmentally friendly adhesive composition according to claim 14, wherein the curing agent is contained in an amount of 0.01 to 5 parts by weight based on 100 parts by weight of the adhesive resin.
16. The environmentally friendly adhesive composition of claim 14, wherein the adhesive composition further comprises a coating solvent.
17. The environmentally friendly adhesive composition according to claim 16, wherein the coating solvent is contained in an amount of 5 to 40 parts by weight based on 100 parts by weight of the adhesive resin.
18. An environmentally friendly adhesive layer formed using the environmentally friendly adhesive resin according to claim 13.
19. The environmentally friendly adhesive layer according to claim 18, wherein the thickness of the adhesive layer is 5 to 500 μm.
Citation Information
Patent Citations
Heat-sensitive self-adhesive composition and heat-sensitive self-adhesive sheet
JP1999005960A
Synthetic resin emulsion, easily water-swelling pressure- sensitive adhesive composition containing the same, and method for producing synthetic resin emulsion
JP2003201306A
Method for manufacturing emulsion pressure-sensitive self-adhesive
JP2004263054A
Solvent-type removable adhesive composition and removable adhesive product
JP2009035708A
Adhesive for optical member, optical member with adhesive layer, image display device, and active energy ray-curable and / or thermosetting adhesive composition for optical member
JP2015074734A